Law, book, culture in the Middle Ages - Gobbitt, Thom (Explorations in medieval culture, 2021)
"In [this book] fifteen contributions are brought together, each taking a detailed view on the role of manuscripts and the written word in legal cultures and literate representations thereof. Four broad thematic approaches exploring the manuscript contexts and reception, of law and legal thought are considered: Law-Books, Law & Society, Legal Practice, and Text & Edition. The studies span the medieval period and reach across western and central Europe, closely considering facets of manuscript culture and legal literacies and practices from what are now Bulgaria, England, France and Germany, Iceland, Ireland, Italy, the Netherlands and Wales"--